The Correlation of Prostate Volume with Uroflowmetry and International Prostatic Symptoms Score (IPSS) on Patient with Benign Prostatic Hyperplasia without Urinary Retention - Arif Rananda; Reny I’tishom; Wahjoe Djatisoesanto; Soetojo (Indian Journal of Forensic Medicine & Toxicology, 2021)
Objective: To value the correlation of Prostate Volume with Uroflowmetry and IPSS on patients with BPHwithout urinary retention that would be conducted at Dr. Soetomo 2015-2017. Method: This research usedretrospective descriptive study using secondary data from medical records to determine the relationshipbetween Prostate Volume (PV) and Uroflowmetry and the International Prostatic Symptom Score (IPSS)of Benign Prostate Hyperplasia (BPH) patients without urinary retention. Uroflowmetry basic parametersis Qmax, Vvoid, and PVR. The sampling technique used the total sampling method that used all existingdata in a certain period. Result: 86 medical records of BPH patients, the age range 45-64 years: 52 patients(60.46%), and the age range> 65 years: 34 patients (39.54%). PV statistical test with Qmax (r = 0.012;p = 0.913), the correlation was not significant. PV with Vvoid (r = 0.112; p = 0.305), the correlation wasnot significant. PV with PVR (r = -0.015; p = 0.892), the correlation was not significant. PV with IPSS (r= 0.048; p = 0.660), the correlation was not significant. Conclusion: There is no correlation on ProstateVolume with Uroflowmetry and IPSS on patient with BPH without urinary retention.